The preferences toward sports of students in institutions of higher education - Špehar, N. (Array, 2008)
This research was conducted to establish preferences toward sports of students in three Zagreb’ s institutions of higher education with majors in humanities and social sciences, and natural sciences and engineering. The sample of 1358 students, specifi cally 443 male and 915 female students, evaluated 59 sports based on the scale of behavioral aims with grades from one through fi ve. Noticeable difference based on gender was established in preferences toward sports. Male students prefer football, table tennis and similar so-called “ adrenalin” sports, while they tend to avoid so-called “ feminine” sports with emphasis on an esthetic component of activity. Female students on the contrary, prefer aerobics, dance, ice-skating and roller-skating. Badminton and individual sports such as cycling and swimming is equally appealing to both female and male students. While there were no signifi cant differences in preferences among female students from different higher education institutions, differentiation were more expressed among male students.